Regulatory Effect of Sea-Buckthorn Procyanidins on Oxidative Injury HUVECs - Lin, Ximeng; Yuen, Michael; Yuen, Tina; Yuen, Hywel; Wang, Min; Peng, Qiang (Frontiers in Nutrition, 2022)
As societal development and population aging, incidence of arteriosclerosis, one of seriously harmful CVD, has continuously risen, which mostly results from endothelial cellular oxidative damage. Procyanidins from sea-buckthorn as a powerful antioxidant, its protective effect on cardiovascular system hasn’t clearly understand yet. In this study, oxidative damaged HUVECs induced by palmitate acid (PA) were used as model and the regulatory effect of procyanidins from sea-buckthorn (SPC) on HUVECs were investigated. The results showed SPC can be absorbed in 12 h by HUVECs and had no detective cytotoxicity to them under 400 μg/L. Also, different concentrations of SPC can increase mitochondrial membrane potential and NO level and decrease LDH leakage in dose-effect relationship, indicating SPC can improve oxidative damage. Besides, western blots and qPCR results analyzed SPC regulation on oxidative injured HUVECs is probably through p38MAPK/NF-κB signal pathway. This study revealed the molecular mechanism of procyanidins in improving endothelial oxidative damage, providing a theoretical foundation for further research on natural bioactive compounds to exert antioxidant activity in body and prevent and improve cardiovascular diseases.